A Strategy to Increase the Competitiveness of Leading Industries in Central Java Province to Face AEC 2015 - Fafurida, Fafurida; Setiawan, Avi Budi; Irmawati, Setyani (International Journal of Economics and Financial Issues, 2016)
The competitiveness of industry in the Central Java Province need to increased in view of the implementation of the AEC is getting closer.The purpose of this research are identifying leading industry in Central Java Province, knowing condition of leading industry competitiveness, and formulating strategy to improve that industry's competitiveness to face AEC 2015. Results of this research shows that leading industry in Central Java Province are beverage, tobacco processing, textile, apparel, wood, printing, furniture and other processing industry. Textile, apparel, wood, printing, and furniture industry has competitiveness, both at national and ASEAN. The strategy formulated among others S-O strategies that optimize the use of local raw materials and the appropriate technologies, W-O strategies that improve production efficiency, S-T strategy is to improve the quality of products and ensure the supply of raw materials continuously and W-T strategy is provide incentives to industry are increasing the proportion of local raw materials. Keywords: AEC; Competitiveness; Leading Industry. JEL Classifications: R11; R50; R58